KUALITAS SOSIS DAGING SAPI YANG DIFORTIFIKASI DENGAN MINYAK IKAN KOD DAN MINYAK JAGUNG DAN DIPROSES MENGGUNAKAN METODE PEMASAKAN YANG BERBEDA - Rio Olympias Sujarwanta (Buletin Peternakan, 2016)
This study was conducted to find out quality of beef sausages fortified with cod and corn oil and processed with different cooking methods. The sausages were made of beef, cod oil, corn oil, tapioca flour, skimmed milk, salt, pepper, garlic, angkak, and ice, with the ratio of cod oil and corn oil of 2.9 : 7.1; 2.4 : 7.6; and 1.9 : 8.1. All sausages ingredients were mixed and then filled in the casing. The raw sausages were cooked using steaming and vacuum steaming for 30 minutes. The sausages were then analyzed for chemical composition (moisture, protein, and fat contents), physical quality (pH, water holding capacity, and tenderness), and fatty acids profile (omega 3 and omega 6 ratio). The data of chemical composition and physical quality were analyzed statistically using analysis of variance (factorial pattern = 3 factors of oil ratio x 2 factors of cooking method) and the differences between means were tested by Duncan’s new Multiple Ranges Test. The data of fatty acids profile were analyzed descriptively. The results showed that the different ratio of cod and corn oils affected the moisture content, protein content, pH, and water holding capacity of sausages (P<0.05). Vacuum steaming increased significantly the moisture content, protein content, fat content, pH, and water holding capacity of sausages (P<0.05). The sausages cooked with vacuum steaming contained higher omega 3 and omega 6 than that of steaming sausages. There were interactions between oil ratio and cooking methods on the moisture content, protein content, pH, and tenderness of sausages (P<0.05). In conclusion, fortification of sausages with cod and corn oil at 2.4 : 7.6 ratio and cooked with vacuum steaming resulting the best quality of sausages.(Key words: Chemical composition, Cod oil, Corn oil, Physical quality, Sausages, Vacuum steaming)